2019
DOI: 10.1111/aor.13380
|View full text |Cite
|
Sign up to set email alerts
|

Durable left ventricular assist device implantation in extremely obese heart failure patients

Abstract: Left ventricular assist devices (LVADs) have improved clinical outcomes and quality of life for those with end‐stage heart failure. However, the costs and risks associated with these devices necessitate appropriate patient selection. LVAD candidates are becoming increasingly more obese and there are conflicting reports regarding obesity’s effect on outcomes. Hence, we sought to evaluate the impact of extreme obesity on clinical outcomes after LVAD placement. Consecutive LVAD implantation patients at our center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Another study including 30 severely obese patients with BMI ≥ 40 kg/m 2 who underwent LVAD implantation found higher rates of pump thrombosis and acute kidney injury in the severely obese group. 76 Though the severely obese patients in this study had higher rates of complications, no differences were found in 30-day or 1-year survival, even after adjusting for age and clinical risk factors. Considering the findings of the meta-analysis by Khan et al 75 in which there was evidence of an obesity paradox in the short-term following LVAD implantation but not at 2 or 3 years, it would be interesting to see if the severely obese patients in this study would also lose their survival advantage at 2 or 3 years or even demonstrate increased mortality at longer-term follow-up.…”
Section: Left Ventricular Assist Devicementioning
confidence: 51%
“…Another study including 30 severely obese patients with BMI ≥ 40 kg/m 2 who underwent LVAD implantation found higher rates of pump thrombosis and acute kidney injury in the severely obese group. 76 Though the severely obese patients in this study had higher rates of complications, no differences were found in 30-day or 1-year survival, even after adjusting for age and clinical risk factors. Considering the findings of the meta-analysis by Khan et al 75 in which there was evidence of an obesity paradox in the short-term following LVAD implantation but not at 2 or 3 years, it would be interesting to see if the severely obese patients in this study would also lose their survival advantage at 2 or 3 years or even demonstrate increased mortality at longer-term follow-up.…”
Section: Left Ventricular Assist Devicementioning
confidence: 51%
“…Multiple studies have evaluated the impact of obesity on post LVAD outcomes, and they found a higher morbidity burden in obese patients, including a higher incidence of pump thrombosis. 18 , 19 The presence of all these conditions is a likely reason for longer hospital stays and higher costs in the hypothyroid group.…”
Section: Discussionmentioning
confidence: 99%
“…So weight reduction should lead to less morbidity. There is no difference in terms of mortality between obese and non obese patients on LVAD (2,(16)(17)(18). There is still little experience with LSG in this specific patient population.…”
Section: Methodsmentioning
confidence: 99%